Different axes of environmental variation explain the presence vs. extent of cooperative nest founding associations in Polistes paper wasps - Sheehan, Michael J; Botero, Carlos A; Hendry, Tory A; Sedio, Brian E; Jandt, Jennifer M; Weiner, Susan; Toth, Amy L; Tibbetts, Elizabeth A; Baalen, Minus (Ecology letters, 2015)
Ecological constraints on independent breeding are recognised as major drivers of cooperative breeding across diverse lineages. How the prevalence and degree of cooperative breeding relates to ecological variation remains unresolved. Using a large data set of cooperative nesting in Polistes wasps we demonstrate that different aspects of cooperative breeding are likely to be driven by different aspects of climate. Whether or not a species forms cooperative groups is associated with greater short‐term temperature fluctuations. In contrast, the number of cooperative foundresses increases in more benign environments with warmer, wetter conditions. The same data set reveals that intraspecific responses to climate variation do not mirror genus‐wide trends and instead are highly heterogeneous among species. Collectively these data suggest that the ecological drivers that lead to the origin or loss of cooperation are different from those that influence the extent of its expression within populations.